Diabetic cardiomyopathy: Mechanisms and new treatment strategies targeting antioxidant signaling pathways - Huynh, Karina; Bernardo, Bianca C.; McMullen, Julie R.; Ritchie, Rebecca H. (Pharmacology & therapeutics (Oxford), 2014)
Cardiovascular disease is the primary cause of morbidity and mortality among the diabetic population. Both experimental and clinical evidence suggest that diabetic subjects are predisposed to a distinct cardiomyopathy, independent of concomitant macro- and microvascular disorders. 'Diabetic cardiomyopathy' is characterized by early impairments in diastolic function, accompanied by the development of cardiomyocyte hypertrophy, myocardial fibrosis and cardiomyocyte apoptosis. The pathophysiology underlying diabetes-induced cardiac damage is complex and multifactorial, with elevated oxidative stress as a key contributor. We now review the current evidence of molecular disturbances present in the diabetic heart, and their role in the development of diabetes-induced impairments in myocardial function and structure. Our focus incorporates both the contribution of increased reactive oxygen species production and reduced antioxidant defenses to diabetic cardiomyopathy, together with modulation of protein signaling pathways and the emerging role of protein O-GlcNAcylation and miRNA dysregulation in the progression of diabetic heart disease. Lastly, we discuss both conventional and novel therapeutic approaches for the treatment of left ventricular dysfunction in diabetic patients, from inhibition of the renin-angiotensin-aldosterone-system, through recent evidence favoring supplementation of endogenous antioxidants for the treatment of diabetic cardiomyopathy. Novel therapeutic strategies, such as gene therapy targeting the phosphoinositide 3-kinase PI3K(p110α) signaling pathway, and miRNA dysregulation, are also reviewed. Targeting redox stress and protective protein signaling pathways may represent a future strategy for combating the ever-increasing incidence of heart failure in the diabetic population.